Vowel duration in alaryngeal speech - G. V.M. Hari Prasad (Journal of All India Institute of Speech and Hearing, 1970)
Intelligibility depends highly on the acoustic, temporal and spectral characteristics of the speech. Various studies have indicated that measures oftime were highly correlated with the overall judged acceptability of esophageal speech.